A guerra colonial contada às crianças: Guilherme de Melo e as irresolúveis ambiguidades - Topa, Francisco (2020)
The colonial war, opposing the Portuguese government to the independence movements in Angola, Guinea-Bissau and Mozambique, was not - as one might expect - a topic in children's literature. There was nevertheless an exception: Menino Candulo, senhor comandante..., by Guilherme de Melo (Ressano Garcia, Mozambique, 01/20/1931 - Lisbon, 06/29/2013). Based on news published in the press in October of the previous year, the book (and its illustrations) reflects the dominant vision of the local white elite, contrasting Frelimo's terrorist malice with the goodness of the Portuguese army. The analysis of this book will be used as an opportunity to consider Guilherme de Melo's odd case: a Mozambican poet and fiction writer until 1975, later converted into a reference in the Portuguese homoerotic narrative.